Non-fluorescent nanoscopic monitoring of a single trapped nanoparticle via nonlinear point sources - Seung Ju Yoon (Nature Portfolio, 2018)
Detection of single nanoparticles or molecules often relies on the attachment of fluorescent labels. Here, the authors demonstrate trapping a single nanoparticle on a bowtie nanoantenna and monitoring via second harmonic generation from the particle.